38-LB: Ex Vivo Immune Cell Function Analysis in Patients with CKD Undergoing Dialysis Treatment Monitors Exercise Treatment Effects on Immunosurveillance - HOFMANN, SUSANNA M.; DINGES, SOPHIA M.; WALTER, MARC; VONKORN, PIA; VONGERSDORFF, GERO D.; ANDING-ROST, KIRSTEN; HALLE, MARTIN (Diabetes (New York, N.Y.), 2023)
Chronic kidney disease (CKD) is marked by a pre-aging and dysfunctional immune system and chronic inflammation. Recent research indicates that chronic physical exercise training (ET) increases regulatory monocytes and T-cells thus modulating the inflammatory status associated with cardio-metabolic diseases. In particular, ET primes monocytes and T-cells towards a less inflammatory phenotype. We hypothesized that intradialytic ET is beneficial to patients with CKD by improving certain immune cell features and decreasing systemic inflammation. We isolated PBMCs from a subset of 18 patients with CKD (58-90 years, 38 % females) enrolled in the prospective intervention trial DiaTT (Dialysis Training Therapy; ClinicalTrials.gov: NCT03885102) at the beginning and after a 12-months intradialytic ET intervention (aerobic endurance + resistance training). Circulating immune cell populations were characterized by FACS. Ex-vivo basal and PMA-induced T-cell activation was determined by cell surface expression analysis of CD69. We found that ET reversed the shift towards intermediate monocytes, a known marker for CKD morbidity and mortality, and nonclassical monocytes in patients with CKD undergoing dialysis treatment. We observed an increase in naïve T-cells and Recent Thymic Emigrants (RTE) indicating an improvement of T-cell function. On T-cells, basal CD69 expression was significantly enhanced and PMA-induced CD69 expression was severely impaired in patients with CKD compared to healthy control subjects (n= 7). When patients with CKD underwent ET this specific T-cell function was restored to normal levels. Here, we show that even in these severely sick patients certain circulating immune cell functions can be regained potentially leading to an enhanced immunosurveillance. Our ex-vivo immune cell characterization and function analysis can be used to monitor exercise treatment effects on systemic inflammation.